High-Temperature Potentiometry: Modulated Response of Ion-Selective Electrodes During HeatPulses - Chumbimuni-Torres, K.; Thammakhet, C.; Galik, M.; Calvo-Marzal, P.; Wu, J.; Bakker, Eric; Flechsig, G.; Wang, J. (American Chemical Society, 2009)
The concept of locally heated polymeric membrane potentiometric sensors is introduced here for the first time. This is accomplished in an all solid state sensor configuration, utilizing poly(3-octylthiophene) as the intermediate layer between the ion-selective membrane and underlying substrate that integrates the heating circuitry. Temperature pulse potentiometry (TPP) gives convenient peak-shaped analytical signals and affords an additional dimension with these sensors. Numerous advances are envisioned that will benefit the field. The heating step is shown to give an increase in the slope of the copperselective electrode from 31 to 43 mV per 10-fold activity change, with a reproducibility of the heated potential pulses of 1% at 10 M copper levels and a potential drift of 0.2 mV/h. Importantly, the magnitude of the potential pulse upon heating the electrode changes as a function of the copper activity, suggesting an attractive way for differential measurement of these devices. The heat pulse is also shown to decrease the detection limit by half an order of magnitude.